The world economy - Maddison, Angus; Maddison, Angus; Maddison, Angus; Organisation for Economic Co-operation and Development. Development Centre; ProQuest (Firm) (Paris, France : Development Centre of the Organisation for Economic Co-operation and Development, 2006)
This publication brings together two reference works by Angus Maddison: The World Economy: A Millennial Perspective, first published in 2001 and The World Economy: Historical Statistics, published in 2003. This new edition contains Statlinks, a service providing access to the underlying data in Excel format. These two volumes bring together estimates of world GDP for the past 2000 years and provide perspective on the rise and fall of economies historically.--Publisher description.
A millennial perspective -- Historical statistics.
"Contains statlinks"--Cover.
"... brings together two reference works by Angus Maddison: The world economy: a millennial perspective, published in 2001 and The world economy: historical statistics, which was released in 2003."--Foreword.
"This new edition contains StatLinks, which allow you to download the tables in Excel format."--P. [4] of cover.
Includes bibliographical references.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Economic history; International economic relations -- History; Population -- History; Income distribution -- History; Economic development -- History; International economic relations -- Statistics; Population -- Statistics; Gross domestic product -- Statistics; Electronic books